Informacijsko vedenje študentov pri uporabi mobilnih naprav - pregled raziskav - Rivo, Ksenija (Knjižnica, 2019)
Mobile devices play an important role in students' lives and thus have great poten-tial for their involvement in future modes of education. Despite its many advantages (portability, convenience), their use for study purposes is still low. The reasons for the (non) use of mobile devices for study purposes have been investigated by several authors, who found that the use of mobile devices to read study e-materials in addition to technological characteristics is influenced by factors related to information behavior. These facts are important for academic libraries because e-resources have become a big part of their (mobile) services. In addition to providing mobile services, their pro-motion is also important, as various studies have shown that students are interested in mobile services but often are not familiar with their offerings in the library. The article deals with an overview of the researches on students' mobile information behavior, which can serve as a good basis for planning and providing mobile services in aca-demic libraries
Keywords: informacijsko vedenje; mobilna tehnologija; študenti; visokošolske knjižnice